2019
DOI: 10.1104/pp.19.00658
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas reinhardtii Exhibits De Facto Constitutive NPQ Capacity in Physiologically Relevant Conditions

Abstract: The photosynthetic apparatus must be able to withstand light conditions that exceed its capacity for carbon fixation. Photosynthetic organisms developed nonphotochemical quenching (NPQ), a process that dissipates excess absorbed light energy as heat and limits the production of reactive oxygen species and cellular damage. In the green alga Chlamydomonas reinhardtii, the LHCSR pigment-binding proteins are essential for NPQ. These complexes are not constitutively present in the thylakoid membranes; however, in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…The energy dissipation Y[NO] also tends to be increasing more in deplete-condition cells after the 4th day, indicating that replete cells are functioning actively toward photochemical reactions. Moreover Y[NO] is defined as a simple indicator for reduced plastoquinone status within photosynthetic membranes, but for high-irradiance microalgae, it is seen that the lower plastoquinone status is minimized, suggesting that the photochemical reactions in normal cells are much more efficient and able to regulate the transportation of photosynthetic electrons compared to the nitrogen-starved cells (Grieco et al, 2012;Nawrocki et al, 2020). During a stress phenomenon the increase in Y[NO] is accompanied by inactivation of PSII reaction centers, which dissipate excitation energy into heat (Maxwell and Johnson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The energy dissipation Y[NO] also tends to be increasing more in deplete-condition cells after the 4th day, indicating that replete cells are functioning actively toward photochemical reactions. Moreover Y[NO] is defined as a simple indicator for reduced plastoquinone status within photosynthetic membranes, but for high-irradiance microalgae, it is seen that the lower plastoquinone status is minimized, suggesting that the photochemical reactions in normal cells are much more efficient and able to regulate the transportation of photosynthetic electrons compared to the nitrogen-starved cells (Grieco et al, 2012;Nawrocki et al, 2020). During a stress phenomenon the increase in Y[NO] is accompanied by inactivation of PSII reaction centers, which dissipate excitation energy into heat (Maxwell and Johnson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Like PsbS the LHCSR3 protein has been proposed to sense the decrease of the pH in the thylakoid lumen during illumination (Ballottari et al, 2016). Nawrocki et al (2019) have shown that LHCSR proteins are responsible for NPQ in Chlamydomonas reinhardtii but that PsbS proteins also play a role in photoprotection. LHCII aggregation is characterized by a shift of the chlorophyll a fluorescence emission to longer wavelengths (Holzwarth et al, 2009) which, interestingly, can also be observed upon the aggregation of FCP complexes in diatoms Lavaud and Lepetit, 2013).…”
Section: Function Of Xanthophyll Cyclesmentioning
confidence: 99%
“…In contrast to plants, where the most rapidly induced component of NPQ is ∆pH dependent heat dissipation (qE), the most rapid response to high light in green algae is a state transition leading to qT-type NPQ. Light-Harvesting Complex Stress-Related proteins 1 and 3 (LHCSR) are constitutively present in C. reinhardtii cells grown in the light (Nawrocki et al 2019 ), and they are activated by light-induced decrease in lumenal pH (Bonente et al 2011 ; Liguori et al 2013 ; Kondo et al 2017 ; Tian et al 2019 ). Active LHCSR3 induces rapid decoupling of LHCII from PSII shortly after the beginning of high-light exposure (Roach and Na 2017 ).…”
Section: Introductionmentioning
confidence: 99%